2015
DOI: 10.2217/pgs.14.166
|View full text |Cite
|
Sign up to set email alerts
|

Donor IL-18 Rs5744247 Polymorphism as a New Biomarker of Tacrolimus Elimination in Chinese Liver Transplant Patients During the Early Post-Transplantation Period: Results from Two Cohort Studies

Abstract: Donor IL-18 rs5744247 polymorphism may influence on tacrolimus elimination. Original submitted 16 July 2014; Revision submitted 12 November 2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Previous studies have reported genetic associations of IL-2, IL-4 and IL-6 with blood concentrations of calcineurin inhibitors [21] . Genetic polymorphisms in IL-18 (eg, rs5744247) and IL-10 (eg, -819 C/T and -592 C/A) can also affect TAC dose requirements [37,38] . However, the exact mechanism by which these polymorphisms affect TAC dose requirements is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported genetic associations of IL-2, IL-4 and IL-6 with blood concentrations of calcineurin inhibitors [21] . Genetic polymorphisms in IL-18 (eg, rs5744247) and IL-10 (eg, -819 C/T and -592 C/A) can also affect TAC dose requirements [37,38] . However, the exact mechanism by which these polymorphisms affect TAC dose requirements is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, researchers investigated the associations of CYP3A5, interleukin (IL)-6, IL-10, and IL-18 genetic polymorphisms with tacrolimus metabolism. [456] Based on our findings, we propose the existence of a gene interaction network that affects tacrolimus pharmacogenomics in patients with HCC after OLT.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies suggested that some gene polymorphisms are associated with drug metabolism. [456] Pharmacogenomics focuses on the relationship between host genetics and drug metabolism. Most previous studies focused on pharmacogenomics regardless of pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Two parameters were checked as confounders, and apart from five studies, others did not assess one or both of them. Appraisal of outcomes revealed that in 23 studies, outcomes of interest were not presented (eg, because of nonsignificant data) or presented improperly (eg, as median) which led to the exclusion of the study from the analyses or obligated us to estimate required data . Eight studies did not continue blood level measurement at specified time points for at least one month or did not mention the time of measurement clearly .…”
Section: Resultsmentioning
confidence: 99%